The Purchasing Decision of Accounting Education Students on the Shopee E-Commerce Platform, Examined from Brand Ambassador, Brand Image, and E-WOM Perspectives - Agustina, Putri Dwi; Jatmika, Surya (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aimed to find out how Brand Ambassadors, Brand Image, and Electronic Word of Mouth influenced the decision to purchase Shopee Accounting Education Students at the Muhammadiyah University of Surakarta. This comparative causal research uses a quantitative approach. The sample was taken from 134 people who responded with a simple random sample method. Data is collected through a questionnaire, and the data analysis method used is double linear regression analysis. The results of the test hypothesis showed that brand ambassadors, brand images, and e-WOM influenced purchasing decisions together. However, in part, Brand Image and e-WOM had a significant positive influence on buying decisions. Whereas Brand Ambassadors did not have a substantial influence on purchasing decisions. The size of the contribution of brand Ambassadores, Brand images, and e-WOM to shopping decisions on Shopee's e-commerce, was 60.2%, while the remaining 39.8% was a constitution of influence upon shopping decisions depending on other variables outside the study.